Stage-specific transcriptomes of the Mussel Mytilus coruscus reveals the developmental Program for the Planktonic to Benthic Transition - Wang, Yu-Qing (2023)
Many marine invertebrate larvae undergo complex morphological and physiological changes during the planktonic—benthic transition (a.k.a. metamorphosis). In this study, transcriptome analysis of different developmental stages was used to uncover the molecular mechanisms underpinning larval settlement and metamorphosis of the mussel, Mytilus coruscus. Analysis of highly upregulated differentially expressed genes (DEGs) at the pediveliger stage revealed enrichment of immune-related genes. The results may indicate that larvae co-opt molecules of the immune system to sense and respond to external chemical cues and neuroendocrine signaling pathways forecast and trigger the response. The upregulation of adhesive protein genes linked to byssal thread secretion indicates the anchoring capacity required for larval settlement arises prior to metamorphosis. The results of gene expression support a role for the immune and neuroendocrine systems in mussel metamorphosis and provide the basis for future studies to disentangle gene networks and the biology of this important lifecycle transformation.